The role of social network (Instagram) in the formation of citizenship identity(Case study of citizens, Isfahan city - Najmeh Karimian Talekhoncheh; Nafiseh Sadr Arahami; Akram Hamidian; Farahnaz Mostafavi Kohnegi (مطالعات رسانه‌های نوین, 2023)
Today, the concept of citizenship as one of the concepts of the modern world is a guide to sustainable human interactions. There is a correlation between variables. The statistical population included all citizens of Isfahan who were Instagram users in 1400, of which 384 people were selected by random cluster sampling. Assessment tools included the citizenship identity questionnaire of Sadr Arhami et al. (2017) and the cousin's Instagram use questionnaire (2015). In this study, 5hypotheses were tested. In order to test the research hypotheses, inferential statistics including Pearson correlation coefficient and structural equations with SPSS25 software were used. The results showed that there is a significant relationship between using the social network Instagram and enjoying citizenship rights. Also, the use of Instagram social network has a positive effect on our identity and the use of Instagram social network has a positive effect on civic commitment with 95% confidence level. Therefore, there is a significant relationship between the use of Instagram social network and citizenship identity with 95% confidence level.